THE AVAATECH XRF CORE SCANNER: TECHNICAL DESCRIPTION AND APPLICATIONS TO NE ATLANTIC SEDIMENTS - Richter T.O.; Van Der Gaast S.; Gieles R.; De Stigter H.C.; De Haas H.; Van Weering T.C.E.; Koster B.; Vaars A. (My University, 2006)
X-ray fluorescence (XRF) core scanning provides rapid high-resolution (down to 1 mm) records of chemical composition on split sediment cores. The measurements are non-destructive and require very limited sample preparation. The new Avaatech XRF CoreScanner, operational since 2002, covers the atomic mass range from A1 to U. Instrument parameters, especially tube voltage, can be adjusted to provide optimum settings for selected elements or sets thereof. Owing to the nature of the surface of split sediment cores, particularly effects resulting from sample inhomogeneity and surface roughness, results are semi-quantitative, yet provide reliable records of the relative variability in elemental composition downcore. Selected case studies from diverse sedimentary settings in the NE Atlantic Ocean illustrate a range of applications of XRF logging data. These include preliminary stratigraphic interpretations (glacial-interglacial cycles), provenance studies of the terrigenous sediment fraction, lithological characterization, early diagenetic processes and distinction between carbonate phases (aragonite v. calcite). © The Geological Society of London 2006.